Preliminary Study of a-value and b-value of Earthquake at Timor Leste Period 1975 – 2022 - Jose da Costa; Sukir Maryanto; Alamsyah Mohammad Juwono; Joanico Pires; Geovanio Pedro da Silva Almeida; Luis Teofilo da Costa (Jurnal Penelitian Pendidikan IPA, 2024)
The utilization of social networks in the formation of Social Chemistry by State-Owned Enterprises (SOEs) in the Meranti Islands as Sociopreneurs is an innovation that enables the optimization of sago potential utilization. This study aims to explore the role of social networks in supporting the success of Rumah BUMN Meranti Islands in marketing sago products through E-Commerce. The research method used is a descriptive qualitative approach through interviews. The results of the study show that the role of social networks in the formation of social chemistry in the use of e-commerce by Rumah BUMN Meranti Islands as a sociopreneur for optimizing the utilization of sago potential demonstrates a significant synergy between digital technology and social dynamics. Rumah BUMN Meranti Islands has successfully leveraged social media platforms such as Facebook, Instagram, and WhatsApp to build close connections with various stakeholders, including sago farmers, artisans, local SMEs, and consumers, through special groups, pages, online discussions, webinars, and Q&A sessions. Active community participation is also encouraged through contests and challenges, which strengthen the sense of ownership among members. With this approach, Rumah BUMN Meranti Islands not only promotes sago products but also creates a dynamic and sustainable ecosystem, where the potential of sago can be optimized through community synergy and technology. This harmonious and constructive interaction reflects the principles of social chemistry, enhancing community cohesion and collective trust, as well as the effectiveness of collaboration and innovation.